Prevalence of Advanced Colorectal Neoplasia in Veterans: Effects of Age, Sex, and Race/Ethnicity. Issue 10 (November 2021) - Imperiale, Thomas F.; Daggy, Joanne K.; Imler, Timothy D.; Sherer, Eric A.; Kahi, Charles J.; Larson, Jason; Cardwell, Jon; Johnson, Cynthia S.; Ahnen, Dennis J.; Antaki, Fadi; Ashley, Christopher; Baffy, Gyorgy; et al.
Abstract : Goal: We sought to quantify the independent effects of age, sex, and race/ethnicity on risk of colorectal cancer (CRC) and advanced neoplasia (AN) in Veterans. Study: We conducted a retrospective, cross-sectional study of Veterans aged 40 to 80 years who had diagnostic or screening colonoscopy between 2002 and 2009 from 1 of 14 Veterans Affairs Medical Centers. Natural language processing identified the most advanced finding and location (proximal, distal). Logistic regression was used to examine the adjusted, independent effects of age, sex, and race, both overall and in screening and diagnostic subgroups. Results: Among 90, 598 Veterans [mean (SD) age 61.7 (9.4) y, 5.2% (n=4673) were women], CRC and AN prevalence was 1.3% (n=1171) and 8.9% (n=8081), respectively. Adjusted CRC risk was higher for diagnostic versus screening colonoscopy [odds ratio (OR)=3.79; 95% confidence interval (CI), 3.19-4.50], increased with age, was numerically (but not statistically) higher for men overall (OR=1.53; 95% CI, 0.97-2.39) and in the screening subgroup (OR=2.24; 95% CI, 0.71-7.05), and was higher overall for Blacks and Hispanics, but not in screening. AN prevalence increased with age, and was present in 9.2% of men and 3.9% of women [adjusted OR=1.90; 95% CI, 1.60-2.25]. AN risk was 11% higher in Blacks than in Whites overall (OR=1.11; 95% CI, 1.04-1.20), was no different in screening, and was lower in Hispanics (OR=0.74; 95% CI, 0.55-0.98). Women had more proximal CRC (63% vs. 39% for men; P =0.03), but there was no difference in proximal AN (38.3% for both genders). Conclusions: Age and race were associated with AN and CRC prevalence. Blacks had a higher overall prevalence of both CRC and AN, but not among screenings. Men had increased risk for AN, while women had a higher proportion of proximal CRC. These findings may be used to tailor when and how Veterans are screened for CRC. Abstract : Supplemental Digital Content is available in the text.